Determinasi Keputusan Pembelian Kosmetika: Studi pada Kelengkapan Produk, Harga, dan Pelayanan - Zumrotul Ulya; Enny Dwi Lestariningsih; Ahmad Lukman Nugraha; Ubbadul Adzkiya; Tyagita Dianingtyas Sudibyo (Green Economics Review, 2025)
This study is motivated by the high number of female Islamic boarding school students (santriwati) in Lasem and the growing presence of cosmetic stores in the area, including Jelita Cosmetic Store located in Karangturi Village, Lasem District, Rembang Regency. These stores aim to meet the cosmetic needs of the santriwati, leading to increased competition and offering consumers more choices. The purpose of this study is to examine the influence of product completeness, price, and service quality on purchasing decisions made by santriwati from Al-Hidayat Al-Ma’shomi Islamic Boarding School who shop at Jelita Cosmetic Store. This research employs an associative quantitative method with a sample of 36 respondents. Data were collected through questionnaires and interviews and analyzed using IBM SPSS Statistics 27 for Windows. Analytical techniques include validity and reliability tests, multiple linear regression, classical assumption tests, model feasibility tests, t-tests, and F-tests. Interview findings revealed that price is the primary factor influencing santriwati to purchase cosmetics at Jelita Store, as it offers more affordable prices compared to other stores. However, product variety and service quality were perceived as lacking. The research results show that product completeness, price, and service quality simultaneously influence purchasing decisions. Partially, only price has a positive and significant effect, while product completeness and service quality do not have a significant influence. The implications of these findings highlight that pricing strategy is a key factor in attracting consumers. Nevertheless, improving product variety and service quality is also essential to enhance customer satisfaction and loyalty.